A novel zinc finger transcription factor, BcMsn2, is involved in growth, development, and virulence in Botrytis cinerea - Lu, Ping; Wang, Ke; Wang, Jiaqi; Xia, Chunbo; Yang, Shu; Ma, Liang; Shi, Haojie (Frontiers in Microbiology, 2023)
Reactive oxygen species (ROS) are important for plant defense against fungal attack. As a necrotrophic fungus, Botrytis cinerea can exploit ROS that originated from both sides of the host and pathogen during interaction to facilitate its infestation. Meanwhile, B. cinerea needs to exert an efficient oxidative stress responsive system to balance the intracellular redox state when encountering deleterious ROS levels. However, the machinery applied by B. cinerea to cope with ROS remains obscure. Herein, we investigated the role of the transcription factor BcMsn2 in regulating B. cinerea redox homeostasis. Disruption of the BcMsn2 gene severely impaired vegetative growth, sclerotium formation, conidial yield, and fungal virulence. The intracellular oxidative homeostasis of the ∆bcmsn2 mutant was disrupted, leading to significantly elevated levels of ROS and reduced activities of enzymes closely associated with oxygen stress, such as catalase (CAT) and superoxide dismutase (SOD). RNA-Seq and qRT-PCR analyses showed remarkable downregulation of the expression of 2 This is a provisional file, not the final typeset article several genes encoding ROS scavenging factors involved in maintaining the redox homeostasis in ∆bcmsn2, suggesting that BcMsn2 functions as a transcriptional regulator of these genes. Our findings indicated that BcMsn2 plays an indispensable role in maintaining the equilibrium of the redox state in B. cinerea, and intracellular ROS serve as signaling molecules that regulate the growth, asexual reproduction, and virulence of this pathogen.